-7(2x-1)+5(3x-2)-7=4-9

Simple and best practice solution for -7(2x-1)+5(3x-2)-7=4-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(2x-1)+5(3x-2)-7=4-9 equation:


Simplifying
-7(2x + -1) + 5(3x + -2) + -7 = 4 + -9

Reorder the terms:
-7(-1 + 2x) + 5(3x + -2) + -7 = 4 + -9
(-1 * -7 + 2x * -7) + 5(3x + -2) + -7 = 4 + -9
(7 + -14x) + 5(3x + -2) + -7 = 4 + -9

Reorder the terms:
7 + -14x + 5(-2 + 3x) + -7 = 4 + -9
7 + -14x + (-2 * 5 + 3x * 5) + -7 = 4 + -9
7 + -14x + (-10 + 15x) + -7 = 4 + -9

Reorder the terms:
7 + -10 + -7 + -14x + 15x = 4 + -9

Combine like terms: 7 + -10 = -3
-3 + -7 + -14x + 15x = 4 + -9

Combine like terms: -3 + -7 = -10
-10 + -14x + 15x = 4 + -9

Combine like terms: -14x + 15x = 1x
-10 + 1x = 4 + -9

Combine like terms: 4 + -9 = -5
-10 + 1x = -5

Solving
-10 + 1x = -5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 1x = -5 + 10

Combine like terms: -10 + 10 = 0
0 + 1x = -5 + 10
1x = -5 + 10

Combine like terms: -5 + 10 = 5
1x = 5

Divide each side by '1'.
x = 5

Simplifying
x = 5

See similar equations:

| 7+5k=5k+1 | | 2x-3=8x-3(1+2x) | | 3x+7=-2x+5 | | 0=-7s+7s | | 4x-35=3+10 | | 5x+bx=7 | | 3(1+5x)-1=-103 | | -8.6q+13.32=-18.4q+6.04+9.1q | | 5x+6x+7=5x-7 | | 4x-2=13x+16 | | 2(15r+10)=-80 | | 17f+8=18f-6 | | 7w-w=6w | | (14x)Y-7=(7x)Y+7 | | 10b-8=10b+7 | | 2(x+3)x=5 | | -1xy=10+2y | | -7-4f=-4f-1 | | 100+y=23 | | 5y+4y-12=0 | | y=-0.3x^2+2.4x+4 | | x^2y-16y^3=0 | | x+-7=10 | | v=35v-16 | | 0=r-r | | 12x+12=11x-44 | | -12(x-0.5)+3=-6x+75 | | 6(4+5)=2f-8 | | 10h=-1+10h | | z=15+2(x+y)findx | | 17x^3+34x^2-85x-102=0 | | -6+8v=5v |

Equations solver categories